Free‐ranging red deer (Cervus elaphus) as carriers of potentially zoonotic Shiga toxin‐producing Escherichia coli. Issue 4 (15th June 2021) - Lauzi, Stefania; Luzzago, Camilla; Chiani, Paola; Michelacci, Valeria; Knijn, Arnold; Pedrotti, Luca; Corlatti, Luca; Buccheri Pederzoli, Clelia; Scavia, Gaia; Morabito, Stefano; Tozzoli, Rosangela
Abstract: Shiga toxin‐producing E. coli (STEC) are zoonotic foodborne pathogens of outmost importance and interest has been raised in recent years to define the potential zoonotic role of wildlife in STEC infection. This study aimed to estimate prevalence of STEC in free‐ranging red deer ( Cervus elaphus ) living in areas with different anthropisation levels and describe the characteristics of strains in order to evaluate the potential risk posed to humans. Two‐hundred one deer faecal samples collected in 2016–2018 from animals of Central Italian Alps were examined by bacteriological analysis and PCR screening of E. coli colonies for stx1, stx2 and eae genes. STEC strains were detected in 40 (19.9%) deer, with significantly higher prevalence in offspring than in yearlings. Whole genome analysis was performed to characterise a subset of 31 STEC strains. The most frequently detected serotype was O146:H28 ( n = 10, 32.3%). Virulotyping showed different stx subtypes combinations, with stx2b ‐only ( n = 15, 48.4%) being the most prevalent. All STEC lacked the eae gene but harbored additional virulence genes, particularly adhesins, toxins and/or other colonisation factors also described in STEC isolated from disease in humans. The most frequently detected genes were astA ( n = 22, 71%), subAB ( n = 21, 68%), iha ( n = 26, 83.9%) and lpfA ( n = 24, 77%). Four hybrid STEC/Enterotoxigenic E. coli strains were also identified. According to the most recent paradigm for pathogenicity assessment of STEC issued by the European Food Safety Authority, our results suggest that red deer are carriers of STEC strains that may have zoonotic potential, regardless of the anthropisation levels. Particular attention should be drawn to these findings while handling and preparing game meat. Furthermore, deer may release STEC in the environment, possibly leading to the contamination of soil and water sources.